2014
DOI: 10.3747/co.21.1698
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Evaluation of Care Plans for Canadian Breast and Head-and-Neck Cancer Survivors

Abstract: advance, auto-populating the templates for the nurses, and creating summary pages for physicians. ConclusionsThe results suggest ways in which scps could help to improve the transition to cancer survivorship and provide starting points for larger feasibility studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 44 publications
(40 reference statements)
0
29
0
Order By: Relevance
“…The U.S. Institute of Medicine called for patients completing their primary treatment for cancer-and for their primary care providers-to be provided with a treatment summary and comprehensive plan for follow-up, with the intent of providing guidance on follow-up care, prevention, and health maintenance 26 . A recent evaluation of the care plans of 36 breast cancer survivors and 21 head-and-neck cancer survivors in Alberta, including interviews with the physicians, nurses, and patients involved, suggested that care plans can enhance communication between survivors and care providers and that survivors appreciate individualized attention and comprehensiveness in a care plan 27 . The importance of providing cancer survivors with individualized information has been reported elsewhere 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…The U.S. Institute of Medicine called for patients completing their primary treatment for cancer-and for their primary care providers-to be provided with a treatment summary and comprehensive plan for follow-up, with the intent of providing guidance on follow-up care, prevention, and health maintenance 26 . A recent evaluation of the care plans of 36 breast cancer survivors and 21 head-and-neck cancer survivors in Alberta, including interviews with the physicians, nurses, and patients involved, suggested that care plans can enhance communication between survivors and care providers and that survivors appreciate individualized attention and comprehensiveness in a care plan 27 . The importance of providing cancer survivors with individualized information has been reported elsewhere 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…For many cancer survivors, ending active treatment leads to uncertainty about their risk of recurrence and the organization of their care moving forward 1,2 . To address these concerns, oncology providers in the United States are mandated at the end of curative-intent treatment to clarify for patients what comes next through the provision of survivor care plans (scps) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The Institute of Medicine (iom) report on cancer survivorship 2 strongly encouraged post-treatment individualized scps to enhance coordinated and quality care while addressing survivors' and primary care providers' (pcps') transition concerns. An scp contains individualized diagnostic and treatment details, follow-up and surveillance guidelines, symptoms of recurrence to monitor, information on health behaviour, coping, and resources 1,2,4 , and some include specific tools supporting health-behaviour-change planning or self-management 1 . Although no jurisdiction or accreditor mandates delivery, Canadian provincial oncology centres are beginning to offer and evaluate scps 1,5,6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations